Jek Nebenne! : A Method of Self-Healing in a Performance-Lecture - Hoirul Hafifi Arung (Abdi Seni, 2021)
ABSTRACTThis artwork thesis depicts a multimedia performance, which combines several media such as photos, videos, sound recordings, installation, diagrams, charts, graphic design, and scientific journals, as well as digital cameras in performance-lecture. The creation practice borrowing the mode of a lecture combined with performance refers to "jek nebenne!" as the director's memory-recollection to start his work practice.The term "jek nebenne!" is not a standard language which means "don't mess with me!", it is used as the director's foothold in connecting a trauma in a family as a result of domestic violence which is reflected in the same experience of his mother, just like the experience of a female masseuse, brick miner, and farmworker for over thirty years in Bangkalan over the behavior of their respective husbands, as well as a shift of function from the feminine to the masculine. "Jek nebenne!" becomes some sort of creation reference which was often said by his mother, haunting him to this day and suspected to be the source of failure. Including the failure to integrate with the two performers who also experienced trauma (sexual and gender) until the show goes on. His position was leaked as a therapist to evacuate from the situation by sharing his sensitive emotion to the public; leaking of conflict concoction, exploration of body and ability, as well as performer's skill through medias mentioned above. The practice of performance-lecture focuses on psychodrama with a shift of dramaturgy from trauma to sensitive and intervening performer and the production team to show that domestic violence creates a prolonged scar. The director fears that the cruising range of his biography trauma will cause him to re-experience the vulnerability and leaving the audience with intricacy. The practice of such shift as a process of evacuation from acute trauma, as a continuation of "jek nebenne!" self-healing method for positive growth of the soul. Keywords: performance-lecture, "jek nebenne!", self-healing method